Synergistic construction of thermally conductive network in polybenzoxazine with boron nitride hybrid fillers - Yi, Wang; Wu, Wei; Drummer, Dietmar; Shen, Wanting; Chao, Liu; Ning, Wang (Materials Research Express, 2019)
Synergistic effect between micrometer boron nitride/nanometer boron nitride (mBN/nBN) at different mass ratio was investigated. Hybrid fillers of mBN/nBN at certain ratio (mBN:nBN = 1:1) performed best synergistic improvement of thermal conductivities of mBN/nBN/polybenzoxazine (mBN/nBN/PBz) composites fabricated via ball-milling followed by a hot-compression method. The effect of hybrid mBN/nBN fillers on thermally conductive coefficient (lambda), curing behavior and thermal stability was also studied. The lambda value was improved from 0.2276 W.m(-1).K-1 for pristine PBz to 0.9196 W.m-K-1.(-1) for (m/n)BN/PBz composites with 25 wt% hybrid filler. Agari model fitting revealed that mBN/nBN hybrid fillers constructed thermally conductive networks much easier than mBN did. The curing behavior and thermal stability of (m/n)BN/PBz composites were dampened with the addition of m/n hybrid fillers. Also, the addition amount of (m/n)BN hybrid filler had great influence on filler alignment in the matrix.
CRIS-Team WoS Importer:2020-03-20